Exploring second graders’ understanding of the text-illustration relationship in picture storybooks and informational picture books - Thomas, Lisa Carol (Kansas State University, 2010)
Our society is increasingly bombarded with visual imagery; therefore, it is important for educators to be knowledgeable about the elements of art and to use our knowledge to help students deepen their reading understanding. Arizpe & Styles (2003) noted that students must be prepared to work with imagery in the future at high levels of competency, yet visual literacy is seldom taught in schools. Children are surrounded with multiple forms of literacy daily and frequently the communication is in a nonverbal format. The purpose of this qualitative case study was to identify textual/visual connections and describe ways the text-illustration relationship can influence understanding for readers in the second grade. This qualitative research study took place in a Department of Defense school in Europe with six second grade students from September 14, 2009 to November 24, 2009. The six student participants were introduced to the basic elements of art—color, shape, line, texture, and value—at the onset of the study. Student participants expressed their textual, visual, and blended textual/visual understanding of four picture storybooks and four informational picture books. Data collection sources included group discussions, student verbal story retellings, student pictorial drawings and retellings, student interviews, observational field notes, teacher email correspondence, and teacher initial/final interviews. Initial analysis was based on Kiefer’s (1995) Functions of Language taxonomy, Kucer and Silva’s (1996:1999) Taxonomy of Artistic Responses and Sipe’s (2008) Categories of Reader Response. The analysis focused on participants’ textual and visual responses and the blending of textual/visual elements. The analysis revealed six emerging Categories of Textual/Visual Understanding including Personal Life Connections, Text Connections, Factual Connections, Predictive Connections, Elemental Connections, and Emotional Connections. The six categories were also reviewed for the dominant category for each student participant and how the textual/visual responses applied to both picture storybooks and informational picture books. Data analysis also revealed the second grade teacher’s perceptions of the text-illustration relationship as a part of the reading process. Student participant benefits included greater student interest and motivation, increased awareness of visual elements in picture storybooks and informational picture books, and higher level thinking expressed through textual/visual connections.
Keywords: Art and literature; Visual literacy; Emergent readers; Picture books; Elementary education; Text-illustration relationship; Education, Curriculum and Instruction (0727); Education, Early Childhood (0518); Education, Elementary (0524)